Modulation by flavonoids of cell multidrug resistance mediated by P-glycoprotein and related ABC transporters. - Di Pietro, A; Conseil, G; Pérez-Victoria, J; Dayan, G; Baubichon-Cortay, H; Trompier, D; Steinfels, E; Jault, J; De Wet, H; Maitrejean, M; Comte, G; Boumendjel, A; et al. (2002)
Cancer cell resistance to chemotherapy is often mediated by overexpression of P-glycoprotein, a plasma membrane ABC (ATP-binding cassette) transporter which extrudes cytotoxic drugs at the expense of ATP hydrolysis. P-glycoprotein (ABCB1, according to the human gene nomenclature committee) consists of two homologous halves each containing a transmembrane domain (TMD) involved in drug binding and efflux, and a cytosolic nucleotide-binding domain (NBD) involved in ATP binding and hydrolysis, with an overall (TMD-NBD)2 domain topology. Homologous ABC multidrug transporters, from the same ABCB family, are found in many species such as Plasmodiumfalciparum and Leishmania spp. protozoa, where they induce resistance to antiparasitic drugs. In yeasts, some ABC transporters involved in resistance to fungicides, such as Saccharomyces cerevisiae Pdr5p and Snq2p, display a different (NBD-TMD)2 domain topology and are classified in another family, ABCG. Much effort has been spent to modulate multidrug resistance in the different species by using specific inhibitors, but generally with little success due to additional cellular targets and/or extrusion of the potential inhibitors. This review shows that due to similarities in function and maybe in three-dimensional organization of the different transporters, common potential modulators have been found. An in vitro 'rational screening' was performed among the large flavonoid family using a four-step procedure: (i) direct binding to purified recombinant cytosolic NBD and/or full-length transporter, (ii) inhibition of ATP hydrolysis and energy-dependent drug interaction with transporter-enriched membranes, (iii) inhibition of cell transporter activity monitored by flow cytometry and (iv) chemosensitization of cell growth. The results indicate that prenylated flavonoids bind with high affinity, and strongly inhibit drug interaction and nucleotide hydrolysis. As such, they constitute promising potential modulators of multidrug resistance.